KOMITMEN PEMERINTAH DAERAH KABUPATEN/KOTA DI SUMATERA BARAT DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL ANAK - Yazfinedi Yazfinedi (Jurnal Good Governance, 2020)
This study is aimed to analyse the commitment of Distric/City in Province governemt in West Sumatera in improving children’s social welfare in West Sumatera Province. From the analysis of West Sumatera Province government budgets for the period 2015-2018, it was found that most District/City Governments has allocated its budget for children’s social welfare programs, however the sum of the budget spent is relatively small. The findings in this paper are expected to increase understanding and provide solutions related to children's social welfare in Indonesia, especially in the West Sumatera province. The findings in this paper are expected to increase understanding and provide solutions related to children's social welfare in Indonesia, especially in the West Sumatera province.Keywords: Budget, Children Welfare, Commitment, West Sumatera